2018
DOI: 10.1097/md.0000000000013114
|View full text |Cite
|
Sign up to set email alerts
|

Large mesenteric hematoma after extracorporeal shock wave lithotripsy for pancreatic stones

Abstract: Rationale:Mesenteric hematoma after extracorporeal shock wave lithotripsy (ESWL) for pancreatic stones is a very rare complication which has never been reported before.Presenting concerns:We reported a case of a 36-year-old male diagnosed as chronic pancreatitis with pancreatic stones and a large pancreatic pseudocyst. He underwent 3 repeated sessions of pancreatic ESWL (P-ESWL). After the last session of P-ESWL, he complained of dizziness. Physical examination revealed a large mass in the right abdomen.Diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…16 Other studies have reported rare complications such as gastric submucosal hematoma 17 and mesenteric hematoma after ESWL. 18 These complications may affect the success of selective deep cannulation and stone clearance under subsequent endoscopic treatment.…”
mentioning
confidence: 99%
“…16 Other studies have reported rare complications such as gastric submucosal hematoma 17 and mesenteric hematoma after ESWL. 18 These complications may affect the success of selective deep cannulation and stone clearance under subsequent endoscopic treatment.…”
mentioning
confidence: 99%
“…The overall complication rate was 6.7%, including pancreatitis, bleeding, infection, steinstrasse, and perforation. [ 6 ] Rare complications have also been reported, such as hepatic subcapsular hematoma, [ 3 ] splenic hematoma, [ 7 ] colonic hematoma, [ 8 ] large mesenteric hematoma, [ 9 ] and pancreaticobiliary fistula. [ 10 ] Lung contusion has been reported after urinary ESWL, [ 11 ] but to our knowledge, lung contusion has never been reported after P-ESWL.…”
Section: Discussionmentioning
confidence: 99%
“…Different from post-ERCP gastrointestinal bleeding, such as duodenal bulb injury or postsphincterotomy bleeding, post-ESWL bleeding is defined as bleeding in a closed chamber due to shock wave damage in peripancreatic organs, including hepatic subcapsular haematoma, mesenteric haematoma, colonic haematoma, gastric submucosal haematoma and renal subcapsular haemorrhage [29][30][31][32][33]. Bleeding often occurs immediately or within a few hours after P-ESWL.…”
Section: Manifestations and Management Of Complicationsmentioning
confidence: 99%